2013
DOI: 10.3390/nu5062222
|View full text |Cite
|
Sign up to set email alerts
|

Iron in Child Obesity. Relationships with Inflammation and Metabolic Risk Factors

Abstract: Iron (Fe) sequestration is described in overweight and in its associated metabolic complications, i.e., metabolic syndrome (MetS) and non-alcoholic liver fatty disease (NAFLD); however, the interactions between Fe, obesity and inflammation make it difficult to recognize the specific role of each of them in the risk of obesity-induced metabolic diseases. Even the usual surrogate marker of Fe stores, ferritin, is influenced by inflammation; therefore, in obese subjects inflammation parameters must be measured to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
2
12
2
2
Order By: Relevance
“…Studies from West show much lower prevalence of iron deficiency state in obese children ranging from 2% to 15.6% [6,7]. This is contrast to studies from Asian sub-continent, where combined prevalence of ID and IDA is noted to be around 36-42% [8,9].…”
Section: The Commonest Infection Was Tuberculosis (Tb)contrasting
confidence: 48%
“…Studies from West show much lower prevalence of iron deficiency state in obese children ranging from 2% to 15.6% [6,7]. This is contrast to studies from Asian sub-continent, where combined prevalence of ID and IDA is noted to be around 36-42% [8,9].…”
Section: The Commonest Infection Was Tuberculosis (Tb)contrasting
confidence: 48%
“…Currently, there is controversy on the association of iron concentrations in the body and its metabolism with the development of the MetS in both genders, both in adults and adolescents. Iron is usually considered as an independent factor for the development of MetS and, thus, not in all cases associated with ceruloplasmin levels [36][37][38][39][40][41].…”
Section: Non Mets Metsmentioning
confidence: 99%
“…A few decades ago, Sullivan proposed the iron hypothesis, suggesting that iron metabolism contributes to inflammation and oxidative stress, which may lead to atherosclerosis and other cardiovascular diseases [5, 6]. In addition, previous epidemiological studies have reported that iron metabolic alteration, such as ferritin or serum iron, which are known as indicators of iron storage, are associated with oxidative stress and adverse lipid concentration in children and adults [79]. Moreover, several studies have reported that transferrin and soluble transferrin receptor (sTfR) are associated with obesity, metabolic syndrome and other cardiovascular risk factors in adults and children [1012].…”
Section: Introductionmentioning
confidence: 99%